The Influence of Workload on the Performance of Administrative Staff at Husada Hospital in 2025 - Putri, Dinda Hafizia; Efkelin, Ria; Karlina, Elin Artha (LPPM Universitas Dhyana Pura, 2025)
The performance of administrative staff plays a vital role in supporting the smooth delivery of healthcare services in hospitals. Poorly managed workloads can decrease both performance and work efficiency. This study aims to determine the influence of workload on the performance of administrative staff at Husada Hospital in 2025. The research employed a quantitative-descriptive approach with a cross-sectional design. Workload was divided into two categories: internal factors (age, gender, nutritional status, health condition, motivation, trust, and job satisfaction) and external factors (job tasks, work organization, and work environment). A total of 53 respondents were selected using the total sampling technique. Data were collected using a Likert-scale-based questionnaire and analyzed using SPSS with multiple linear regression. The analysis showed that most variables had no significant effect on performance, except for four: job trust (p = 0.004), job satisfaction (p = 0.024), work organization (p = 0.002), and work environment (p = 0.010). Job trust and work organization had a positive effect on performance, while job satisfaction had a negative effect. The study concludes that psychological factors and work systems are more influential in determining performance than physical workload. It is recommended that hospital management strengthen organizational structure, create a supportive work environment, and proportionally enhance trust and job satisfaction to maintain optimal staff performance.